Variação anual da diversidade e produção secundária de Rotifera do reservatório da UHE de Furnas-MG, Brasil - Negreiros, Natalia Felix (2010)
The UHE-Furnas is a reservoir built in 1963 for hydroelectricity generation, but also exploited for multiple purposes. In the last decades it has been subject to continuous antropic impacts as the discharges of domestic and industrial non-treated effluents and the agricultural runoff, thus undergoing progressive nutrient enrichment. Rotifera is an important component group of the zooplankton community, playing relevant role in the transfer of energy and matter in freshwater food chains. Studies on their diversity and productivity can contribute to the understanding of the reservoir as a whole and contribute for the conservation of aquatic biota. The objective of this work was to analyze the spatial seasonal changes of Rotifera species composition, diversity and production, verifying its relationships with the abiotic factors. Rotifera assemblages were sampled monthly in four localities and six points at the Sapucaí compartment of Furnas Reservoir, including four points in the limnetic and two in the littoral region, during the period between August 2006 and July 2007. The main physical and chemical variables were measured in situ and samples were taken for nutrients and chlorophyll a quantification. The Sapucaí compartment had low nutrient concentrations characterizing an oligotrophic system. The Rotifera assemblage was composed by 51 taxa of common occurrence in tropical regions. The highest species richness and population equitability were recorded in the dry period, but there were no significant changes in assemblages composition among sites. Mean production was 31.79 μg PS. m-3.day-1 in the rainy season and 14.27 μgPS. m-3.day-1. The species that contributed most to the production were Conochilus unicornis and Trichocerca chattoni, in the rainy season and C. unicornis, Plationus patulus and Collotheca sp in the dry period. The highest values were recorded in spring-summer seasons, realted to the increases on phytoplankton biomass. The mean P:B ratio was 0.51 corresponding to a turnover time of 1.96 days. Production values obtained for Rotifera were in the range of values reported in the literature for this group, in other oligotrophic reservoirs. Despite its small sizes and biomass when compared to other zooplankton groups, Rotifera assemblages had high biomass turnover rates thus playing important role in nutrient cycling and energy transfer in UHE-Furnas Reservoir.